The Effect of Leaflet-Based Health Education on Adolescent Girls Knowledge of Anemia Prevention - Nurfadhila Nurfadhila; Sumiyati Sumiyati; Rusni Safitry (JURNAL KESEHATAN STIKes MUHAMMADIYAH CIAMIS, 2025)
Anemia is a condition characterized by hemoglobin (Hb) levels below the normal range. It remains a prevalent public health problem among adolescent girls in developing countries. This study aimed to analyze the effect of health education using leaflets on adolescent girls’ knowledge of anemia prevention. The method use is a quasi-experimental one-group pretest-posttest design was conducted among 69 female students at SMAN 1 Polewali Mandar using a validated questionnaire. Data were analyzed using the Wilcoxon Signed Rank Test. Results showed a significant increase in knowledge scores from 39.13 to 91.74 (p<0.001). The study concludes that leaflet-based health education effectively improves anemia prevention knowledge among adolescent girls